2016
DOI: 10.1039/c6ra11408c
|View full text |Cite
|
Sign up to set email alerts
|

TfOH-mediated [2 + 2 + 2] cycloadditions of ynamides with two discrete nitriles: synthesis of 4-aminopyrimidine derivatives

Abstract: In this study, a concise and atom-economical TfOH-mediated [2 + 2 + 2] cycloaddition of ynamides with two discrete nitriles is developed to synthesize multi-substituted 4-aminopyrimidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 44 publications
1
16
0
1
Order By: Relevance
“…13 C NMR [101 MHz, CDCl 3 ]: δ = 14.2, 21.8, 38.5, 61.6, 66.0, 83.5, 128.0, 130.2, 133.0, 145.8, 154.1 ppm. These data were in accordance to those reported in the literature …”
Section: Methodssupporting
confidence: 93%
“…13 C NMR [101 MHz, CDCl 3 ]: δ = 14.2, 21.8, 38.5, 61.6, 66.0, 83.5, 128.0, 130.2, 133.0, 145.8, 154.1 ppm. These data were in accordance to those reported in the literature …”
Section: Methodssupporting
confidence: 93%
“…14 Besides, the condensation of aldehydes, ketones with NH 4 OAc, 15 or of 1,3-diketones, aldehydes, and NH 4 OAc 16 also afforded pyrimidines. It was also demonstrated that the reaction of alkynes and nitriles in the presence of Lewis acids 17 or a cyclization of ketones with two molecules of nitriles provided the pyrimidine skeleton. 18 Recently, Fan and co-workers have reported a methodology for the synthesis of pyrimidines from amidines and ketones using DMF as one carbon source through C(sp 3 )−H activation mediated by TBHP (tert-butyl hydroperoxide) (Scheme 1a).…”
Section: ■ Introductionmentioning
confidence: 99%
“…图式 70 炔酰胺参与的[3+2]环加成反应合成氨基噁唑 Scheme 70 Synthesis of aminooxazoles by [3+2] cycloaddition of ynamides 2019 年, 李清江和王洪根等 [75] [85] 和蔡明中 [86] 等报道了类似的 Au(I)催化炔 酰胺与腈类化合物的[2+2+2]环加成反应, 并研究其 机理. 唐宇等 [87]…”
Section: 关环复分解反应unclassified